Review of 1971/11/19 Concert at Barber Institute of Fine Arts (University of Birmingham) "Bell Piece ’71" by Annea Lockwood and David Jones - Laycock, Jolyon (Contact: A Journal for Contemporary Music (1971-1990), 1972)